Activating Transition Metal Dichalcogenides by Substitutional Nitrogen‐Doping for Potential ORR Electrocatalysts. Issue 24 (11th October 2018) - Singh, Yashpal; Back, Seoin; Jung, Yousung
Abstract: One of the challenging goals in the large‐scale realization of hydrogen‐based fuel cells is to replace or minimize the use of expensive Pt‐based electrocatalysts to reduce molecular oxygen at the cathode. Recently, non‐metal doped nanosheets of transition metal dichalcogenides (TMDs) have emerged as a promising Pt‐free electrocatalyst for hydrogen evolution reaction. Herein, we investigate the potential of nitrogen‐ and phosphorus‐ (N‐ and P‐) doped TMDs (MoS2, MoSe2, WS2, and WSe2 ) as high‐performing electrocatalysts for ORR using first principle calculations, motivated by recent experimental advances to incorporate single S/Se vacancies on the surface of TMD monolayers using electrochemical methods. We observed a strong hybridization of p‐ orbitals of N/P atom with the p‐ and d‐ orbitals of neighbouring S/Se and Mo/W atoms, respectively, activating pristine TMDs by increasing density of states near Fermi‐level. Based on the free energy profiles of the four‐electron reduction process, we expect that N‐TMDs to be efficient in catalyzing ORR, whereas, too strong binding of reaction intermediates prevents ORR on P‐TMDs. Among the candidates considered, N‐WS2 is found to be a promising TMD as ORR catalyst with the overpotential as low as 0.31 V, stimulating further experimental studies. Abstract : The potential of N‐ and P‐doped transition metal transition metal dichalcogenides (TMDs) as electrocatalysts for oxygen reduction is investigated using first principle calculations. Based on the free energy profiles of the four‐electron reduction process, it is expected that N‐TMDs to be efficient in catalyzing ORR, whereas, too strong binding of reaction intermediates prevents ORR on P‐TMDs, stimulating further experimental studies.